Effects of Benzo[a]Pyrene Exposure on Lung Cancer: A Mechanistic Study of Epigenetic m6A Levels and YTHDF1 - Siyi Xu; Jie Li; Sheng Yang; Panpan Yang; Yiru Niu; Yiling Ge; Geyu Liang (Toxics)
Benzo[a]pyrene, as the primary component of air pollutants, has been implicated in the pathogenesis of non-small-cell lung cancer (NSCLC). As an m6A reader that facilitates mRNA translation, YTHDF1 serves as a crucial regulator in tumor progression. Therefore, we established Benzo[a]pyrene(B[a]P)-induced bronchial epithelial malignant transformed cells (HBE-P35) to simulate the precancerous lesions of NSCLC and investigated the regulatory axis of YTHDF1 in both HBE-P35 and A549 lung cancer cells. A high level of m6A expression was detected in both HBE-P35 and A549 cells. Over-expression of YTHDF1 was observed in NSCLC tissues and correlated with poor overall survival in NSCLC patients. TMT labeling-based proteomic analysis and clinical lung tissue microarray assays demonstrated that CDK6 and MAP3K6 were positively correlated with YTHDF1 expression. MeRIP and RIP analyses revealed that YTHDF1 mediates the m6A-dependent regulation of CDK6 and MAP3K6 protein expression. The acquisition and deletion of miR-139/145-5p, along with luciferase reporter gene assays, demonstrated that miR-139-5p can target YTHDF1. Therefore, we conclude that YTHDF1 regulates CDK6 and MAP3K6 through m6A in B[a]P-induced HBE-P35 and A549 cells, providing a potential target for lung cancer treatment.